Treasures from the dust - Eisenberg, Azriel Louis 1903-1985; Elkins, Dov P. (Abelard-Schuman, 1972)
Describes the technical aspects of several important archaeological digs in the Middle East and what their discoveries have revealed about ancient civilizations.